ANALISIS YURIDIS PERATURAN DAERAH DKI JAKARTA NOMOR 2 TAHUN 2020 TENTANG PENANGGULANGAN CORONA VIRUS DISEASE 2019 - Kristianingsih, Reny (Lex Journal: Kajian Hukum & Keadilan, 2022)
The stipulation of DKI Jakarta Regional Regulation Number 2 of 2020 dated November 12, 2020 concerning Handling Corona Virus Disease 2019 is one proof of the seriousness of the DKI Jakarta Regional Government in dealing with the 2019 Corona Virus Disease pandemic and reducing the number of confirmed cases of Corona Virus Disease 2019 patients in the DKI Jakarta area. This research uses a descriptive analysis research method with a normative juridical approach Article 30 of Regional Regulation Number 2 of 2020 as a legal umbrella that can guarantee the health, safety and welfare of the community even though in its application not optimal and the content of the normative material is synchronized with the normative material of the legislation above. Keywords: Combating Corona Virusin DKI Jakarta Regional Regulation Number 2 of 2020